Peripheral mechanisms in tremor after traumatic neck injury. Issue 5 (1st November 2002) - Hashimoto, T; Sato, H; Shindo, M; Hayashi, R; Ikeda, S
Abstract : Tremor is a rare manifestation after neck injury, and its physiological mechanism has not been elucidated. We studied the effects of torque loading and ischaemic nerve block on coarse postural tremor in the right upper extremity, which had developed in association with a C7–C8 radiculopathy after traumatic neck injury in a 55 year old man. Loading reduced the tremor frequency from 6.1 Hz to 4.2 Hz with corresponding electromyography (EMG) bursts at the same frequencies as the tremor. Ischaemic nerve block also reduced the tremor frequency from 6.2 Hz to 2.8 Hz, and the time course of the frequency was not in parallel with that of the size of the maximal M wave. A significant reduction of the tremor frequency by loading and ischaemic nerve block indicates a mechanical reflex mechanism underlying the tremor, and association of synchronous EMG bursts suggests an increase in gain in the stretch reflex loop. The stretch reflex loop plays an important role in generation of oscillation in tremor after neck injury.